Translating Evidence-Based Program Recommendations into Action: The Design, Testing, and Scaling Up of the Behavior Change Strategy EsIAN in Mexico. (3rd December 2019) - Bonvecchio Arenas, Anabelle; González, Wendy; Théodore, Florence L; Lozada-Tequeanes, Ana Lilia; Garcia-Guerra, Armando; Alvarado, Rocio; Fernández-Gaxiola, Ana C; Rawlinson, Cloe J; de la Vega, Alejandría Villa; Neufeld, Lynnette M
ABSTRACT: Background: The Integrated Strategy for Attention to Nutrition (EsIAN in Spanish) is a national strategy within Mexico's conditional cash transfer program (initially Progresa, then Oportunidades, then Prospera, CCT-POP) designed to strengthen the health and nutrition component, address the nutrition transition, and improve the health and nutritional status of its beneficiaries, through 3 main components: 1 ) procurement of functioning equipment to primary health care (PHC) units; 2 ) providing free micronutrient supplements to beneficiary women and children; 3 ) implementing a behavior change communication (BCC) strategy and a training system for PHC providers (PHCPs). Objective: We aim to describe the iterative process and evidence-based approach used to design and roll-out the EsIAN at scale, by focusing on the BCC component. Methods: The BCC strategy was developed by following an iterative process through the following phases: situational analysis, formative research and design of the BCC strategy (using the socioecological framework and the social marketing approach), large-scale feasibility study, redesign, and national scale-up. Results: The review and formative research revealed several barriers and issues that limited program coverage, utilization, and acceptance. These included misconceptions about pregnancy and infant feeding, nonalignment of practices with international recommendations, and lack of knowledge on nutrition and related topics, among others. These results were used to identify priority behaviors and elaborate key messages for mothers/caregivers and providers to develop the BCC strategy. The feasibility study resulted in significant improvements in PHCPs' knowledge, counseling (breastfeeding, and supplement use and consumption), and caregivers' complementary feeding behaviors, and highlighted several design and delivery aspects that needed strengthening. Based on these findings, the BCC strategy was adapted prior to a national scale-up. Conclusions: The theory-based iterative approach resulted in the identification of specific actions to target, and approaches to do so, as part of the design and roll-out of the BCC strategy at scale.